Asghar Ali Engineer: Islam dan Hak-hak Perempuan - Maulidah, Hilma Sa'diatul; Albab, Moch. Vaiz Ulul (Maliki Interdisciplinary Journal, 2024)
Asghar Ali Engineer is a prominent scholar and activist who focuses on social reform and gender equality therein. Apart from that, he also uses Islamic texts such as the Koran and hadith to support women's rights to be realized. Ali emphasized the importance of ijtihad and rejection of taqlid to promote a more progressive and inclusive understanding of the role of women in Islam.